Uncovering Two Principles of Multivariate Hierarchical Metal–Organic Framework Synthesis via Retrosynthetic Design - Feng, Liang (ACS Cent Sci, 2018)
[Image: see text] Multivariate (MTV) hierarchical metal–organic frameworks (MOFs), which contain multiple regions arranged in ordered structures, show promise for applications such as gas separation, size-selective catalysis, and controlled drug delivery. However, the complexity of these hierarchical MOFs is limited by a lack of control during framework assembly. Herein, we report the controlled generation of hierarchical MOF-on-MOF structural formation under the guidance of two design principles, surface functionalization and retrosynthetic techniques for stability control. Accordingly, the tunability of spatial distributions, compositions, and crystal sizes has been achieved in these hierarchical systems. The resulting MOF-on-MOF hierarchical structures represent a unique crystalline porous material which contains a controllable distribution of functional groups and metal clusters that are associated together within a framework composite. This general synthetic approach not only expands the scope and tunability of the traditional MTV strategy to multicomponent materials, but also offers a facile route to introduce variants and sequences to sophisticated three-dimensional hierarchical and cooperative systems. As a proof of concept, the photothermal effects of a porphyrinic core-MOF are exploited to trigger the controlled guest release from a shell-MOF with high guest capacity, highlighting the integrated cooperative behaviors in multivariate hierarchical systems.